Kekerasan Polisi yang digambarkan dalam Puisi Jericho Brown “Bullet Points” - Yan Ardian Subhan; Umi Hani (LITERATUS, 2022)
The aim of this study is to analyze depiction of police violence in a poem Bullet Points (2019) by Jericho Brown. Data collection and analysis used qualitative research that explains the data into essay description. This study used racial discrimination theory by Loomba (2015). The results of this study show that in Jericho Brown poem portray issues of police violence, such as received racial discrimination act countless times, positioned in lower classes of economic, and experienced the practice of killing.